"Before the War, Life Was Much Brighter and Happier than Today": Letters from French War Orphans, 1915–1922. Issue 3 (1st December 2020) - Keenan, Bethany S.
Abstract: This article examines a previously unstudied collection of letters from French World War I orphans and widows, published in US newspapers from 1915 to 1922, as a result of the US humanitarian effort Fatherless Children of France (FCOF). Through the analysis of the letters' content and style, the article illuminates the lived experience of bereaved lower-income French families, notably highlighting the significance of grief and the impact of paternal loss on economic status, bringing out new evidence on how women and children experienced the war, as well as showing how humanitarian efforts connected French and American civilians during the war period.